Corneal Ulcer, What Should We Do as a General Practitioner? (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2022)
Introduction : Corneal ulcer with hypopyon is a serious corneal infection and a common potential cause of vision loss. It is profoundly predominant and also the common cause of visual impairment and preventable ocular morbidity around the world. Management of corneal ulcers with hypopyon requires a referral and multimodal treatment including pharmacological intervention. Case Report : A case of a 56-year-old male patient who presented with a chief complaint of blurry vision, red, and pain in the right eye since 3 weeks prior. There was a history of the right eye scratched by coconut husk. He complains of a whitish plaque 2 weeks earlier. Previous medical treatment history was denied. Visual acuity of the right eye was 1/300 and the left eye was 20/20. Eye examination revealed a corneal ulcer with a 2mm hypopyon, conjunctival and ciliary injection. This patient was diagnosed with a corneal ulcer with hypopyon. Treatment begins with oral antifungal, eyedrop, and oral antibiotics. The patient was planned to be referred to the ophthalmologist, but the patient refused. Conclusion: Corneal ulcer with a hypopyon could lead to sight-threatening complications such as perforation and endophthalmitis. General practitioners should be aware to early diagnose and give initial treatment to the patient. Appropriate referral and education given to the patients are necessary to avoid complications or prevent severe cases..